2009
DOI: 10.3233/jad-2009-1023
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's Disease-Diabetes Angle: Inevitable Fate of Aging or Metabolic Imbalance Limiting Successful Aging

Abstract: Modern societies face the increasing burden of agerelated diseases, in particular Alzheimer's disease (AD) and type 2 diabetes (T2D). While numerous epidemiological studies have described the incidence of both diseases in the Western world and extensively defined common environmental risk factors, only little is known on the pathomechanisms linking both diseases [1][2][3]. Thus, it is not yet clear whether both diseases represent the endpoint of aged, exhausted, and dysfunctional cells having reached their max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recent evidences suggest that age-relate cofactors play a key function in mediating the toxicity of A β at early, AD stages. One of the risk factors is diabetes mellitus (DM) and several studies demonstrated a link between DM and AD [ 9 11 ]. In agreement, both hyperglycemia in DM and age-dependent oxidative stress induce the formation of advanced glycation end products (AGEs) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidences suggest that age-relate cofactors play a key function in mediating the toxicity of A β at early, AD stages. One of the risk factors is diabetes mellitus (DM) and several studies demonstrated a link between DM and AD [ 9 11 ]. In agreement, both hyperglycemia in DM and age-dependent oxidative stress induce the formation of advanced glycation end products (AGEs) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other plausible common pathogenic component in both AD and T2D is inflammation (Bierhaus and Nawroth 2009). It has been shown that hyperinsulinemia, induced by peripheral insulin administration, elevated cerebrospinal fluid (CSF) levels of tumor necrosis factoralpha (TNF-α), IL-1α, IL-1β and IL-6, and stimulated amyloidogenesis in healthy volunteers 4 (Fishel et al 2005).…”
mentioning
confidence: 99%